North Pontic Archaeology : Recent Discoveries and Studies - Tsetskhladze, G.R., (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
This volume deals with the classical archaeology of the northern Black Sea littoral, discussing excavations and studies conducted by Russian, Ukrainian, German, Czech and British archaeologists and classicists over the last 10-12 years. It presents the results of excavations of such sites as Berezan, Nikonion, the chora of Olbia, the chora of Chersonesus, rural settlements of the European Bosporus, sites on the Taman Peninsula, etc. Several articles discuss the Scythians and other local peoples, as well as particular objects. This 6th volume of Colloquia Pontica publishes much previously unknown material, and gives a clear picture of the achievements of scholarship in the study of the North Pontic Region. Included are book reviews and an eloborate listing of new publications. The book is very richly illustrated.